2018
DOI: 10.1080/17461391.2018.1438521
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between skeletal muscle contractile properties and power production capacity in female Olympic rugby players

Abstract: This study aimed to determine which contractile properties measured by tensiomyography (TMG) could better differentiate athletes with high- and low-power values, as well as to analyse the relationship between contractile properties and power production capacity. The contractile properties of the vastus medialis (VM), rectus femoris (RF) and vastus lateralis (VL) of an Olympic women's Rugby Sevens team (n = 14) were analysed before a Wingate test in which their peak power output (PPO) was determined. Athletes w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…Likewise, the relationship between contractile properties and rugby player’s power measured thought a Wingate Test shows negative correlations between power and Dm, Vd and Td of the VL (r =−0.75, r = −0.70 and r =−0.61, respectively), without finding significant relationships between power developed in the test and contractile properties of RF and VM 47…”
Section: Relationship Of Contractile Properties With Sports Performancementioning
confidence: 95%
“…Likewise, the relationship between contractile properties and rugby player’s power measured thought a Wingate Test shows negative correlations between power and Dm, Vd and Td of the VL (r =−0.75, r = −0.70 and r =−0.61, respectively), without finding significant relationships between power developed in the test and contractile properties of RF and VM 47…”
Section: Relationship Of Contractile Properties With Sports Performancementioning
confidence: 95%
“…In contrast to the GL and GM, the Dm and Vd of the VL were significantly lower in the unilateral LLA than in the control group, indicative of a higher muscle stiffness of the VL in the intact limb. 19 Valenzuela et al 19 identified an association between higher muscle stiffness (lower Dm or Vd) of the VL and a higher peak power output during pedaling performance, with the muscle stiffness of the VL providing the best predictor of power production capacity. Our findings of a greater stiffness of the VL are indicative of the high muscle power output required of the intact lower limb in a unilateral LLA.…”
Section: Discussionmentioning
confidence: 99%
“…Three of these studies (43% of 7 studies) were performed in rugby sevens with an international/Olympic cohort. [155][156][157] Of the remaining four studies, the rugby code was not reported, and the cohort was either varsity (14%), 158 subelite and elite (14%), 159 international (14%) 160 or not reported (14%). 161 Studies investigated a range of physiological-themed topics.…”
Section: Physiologymentioning
confidence: 99%